Report on the fur trade accounts [electronic resource] - Hudson's Bay Company. ([London? : s.n., 1879)
Tables. Signed: George J. Goschen, John Rose, Edwd. Hamilton. Dated: Hudson's Bay House, London, July 1879. At head of title: Confidential. Electronic reproduction. Mode of access: Internet. 44